The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00332-003-0582-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Computational Singular Perturbation Reduction Method for Chemical Kinetics

Abstract: Summary. This article is concerned with the asymptotic accuracy of the Computational Singular Perturbation (CSP) method developed by Lam and Goussis [The CSP method for simplifying kinetics, Int. J. Chem. Kin. 26 (1994) to reduce the dimensionality of a system of chemical kinetics equations. The method, which is generally applicable to multiple-time scale problems arising in a broad array of scientific disciplines, exploits the presence of disparate time scales to model the dynamics by an evolution equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0
14

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 33 publications
2
104
0
14
Order By: Relevance
“…(4.8)-(4.9), CSP performs the updating in two steps; the first step involves the matrices U , the second the matrices L. In [22] and [23], we showed that the two steps play different roles and that, if one is interested solely in approximating the slow manifold, one may as well skip the second step. The slow manifold constructed with the so-called one-step CSP [22], which involves only the matrices U , has the same asymptotic accuracy as the slow manifold constructed with CSP.…”
Section: The Principle Of Cspmentioning
confidence: 98%
See 3 more Smart Citations
“…(4.8)-(4.9), CSP performs the updating in two steps; the first step involves the matrices U , the second the matrices L. In [22] and [23], we showed that the two steps play different roles and that, if one is interested solely in approximating the slow manifold, one may as well skip the second step. The slow manifold constructed with the so-called one-step CSP [22], which involves only the matrices U , has the same asymptotic accuracy as the slow manifold constructed with CSP.…”
Section: The Principle Of Cspmentioning
confidence: 98%
“…Many techniques have been proposed for this purpose, especially in the chemical kinetics literature; see the references in [8,22,23]. Generally, they involve the construction of a coordinate system where the slow manifold has a simple functional representation-the ideal system being one where a number of components (the "fast" components) of the state vector are identically zero, as in the Fenichel normal form [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure for generating and numerically solving these DAE models is known as computational singular perturbation (CSP). A discussion of the CSP method is provided in [16,26,27]. Whether one is numerically solving the full model or the reduced, slow-timescale DAE model, it is generally assumed that all kinetic parameters are known.…”
Section: Solving the Full Or Reduced Model Numericallymentioning
confidence: 99%